Podnebna tipizacija Slovenije po podatkih za obdobje 1991–2020 - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
This article presents a climate classification for Slovenia for the climatological period 1991–2020. It is based on the Köppen-Geiger classification, but this classification is too coarse-grained to show all the specific climatic features of Slovenia. Taking into account additional temperature and precipitation criteria, we divided the Slovenian climate into four basic types with nine subtypes: moderate Mediterranean (coastal and inland), moderate continental (of northeast, east and southeast, and central Slovenia), mountain (of higher and lower mountains) and submontane climates (very humid and humid).
Keywords: climate classification; climate types; climatogeography; klimatogeografija; Köppen-Geiger climate classification; Köppen-Geigerjeva klasifikacija; podnebne klasifikacije; podnebni tipi; Slovenia; Slovenija